The War in Vietnam and the United States Balance of Payments - Dudley, Leonard; Passell, Peter (The Review of Economics and Statistics, 1968)
IT is generally recognized that the international monetary crises of late 1967 and early 1968 were precipitated by large, continuing deficits in the United States balance of payments. Underlying these deficits was a steady erosion of the United States surplus on current account, which fell from 8.5 billion dollars in 1964 to 4.8 billion dollars in 1967. Despite government programs restricting foreign investment by United States residents,1 therefore, the overall deficit on a liquidity basis reached a level of 3.6 billion dollars in 1967. The resulting outflow of dollars and gold greatly reduced the confidence of speculators and central banks in the ability of the United States to maintain the international value of its currency. It is of course no coincidence that this deterioration in the current account position of the United States accompanied a rapid expansion of its military commitments in Southeast Asia. But the amount of the deterioration which may be attributed to the War in Vietnam is a point at issue. The Administration has estimated the direct foreign exchange cost of the War to be about 1.5 billion dollars.2 Many have argued, however, that if secondary and indirect effects are taken into account, the total impact on the balance of payments has been much greater. In this paper, we shall attempt to reach a more satisfactory estimate -or range of estimates -of the total effect of the War on the balance of payments. In so doing, we shall try to answer the question: What would the United States balance on current account have been in 1967 if real expenditures had been lower by the amount channeled into the military effort in Southeast Asia? The wording of this question perhaps requires further explanation. We shall assume that the multiplier effects of this hypothetical difference in expenditures could have been completely and precisely offset by monetary and fiscal policy. Thus we suggest that in the absence of the military build-up, expenditures for consumption, investment and government purposes other than the War would have been identical with those that actually occurred. In addition, it must be recognized that part of the increase in military expenditures would have been spent even without the Vietnam War build-up. The men now serving in the armed forces would have eaten, for example, regardless of whether they were in military or civilian roles. For this reason, we exclude domestic expenditures on military pay, provisions and accommodation from our calculations, and consider only those expenditures which may clearly be assigned to the expanded campaign in Vietnam.3 One may note several possible effects which this military spending may have had on the United States current account balance: 1) Increased direct foreign purchases of food, services and finished goods to supply the military effort. 2) Greater purchases of foreign goods to be used as inputs in United States defense production. 3) Deterioration in the United States net exports, due to both war-stimulated inflation and to supply bottlenecks in those sectors of production most affected by the increased spending. In the following sections, we shall examine each of these effects in turn. By summing the three components we hope to provide a relatively accurate and comprehensive picture of the balance of payments impact of the War. * The authors are grateful to Robert Triffin and Richard Cooper for their helpful comments and suggestions. 1 Note that this practice of restricting capital cannot be continued indefinitely without worsening the balance on current account, because it will of course reduce United States earning assets abroad. 2 U.S. Treasury Department, Maintaining the Strength of the U.S. Dollar in a Strong Free World Economy (Washington, 1968), p. 103. 'As noted below, foreign military purchases of food, etc., by the United States will be included in the direct current account impact of the War.